Toxoplasma gondii-induced host cellular cell cycle dysregulation is linked to chromosome missegregation and cytokinesis failure in primary endothelial host cells - Zahady D. Velásquez (Nature Portfolio, 2019)
Abstract Toxoplasma gondii is a zoonotic and intracellular parasite with fast proliferating properties leading to rapid host cell lysis. T. gondii modulates its host cell on numerous functional levels. T. gondii was previously reported to influence host cellular cell cycle and to dampen host cell division. By using primary endothelial host cells, we show for the first time that T. gondii tachyzoite infections led to increased host cell proliferation and to an enhanced number of multi-nucleated host cells. As detected on DNA content level, parasite infections induced a G2/M cell cycle arrest without affecting expression of G2-specific cyclin B1. In line, parasite-driven impairment mainly concerned mitotic phase of host cells by propagating several functional alterations, such as chromosome segregation errors, mitotic spindle alteration and blockage of cytokinesis progression, with the latter most likely being mediated by the downregulation of the Aurora B kinase expression.